Texnik tizimlardagi masalalarni yechishda Matlab dasturining imkoniyatlaridan foydalanish (SCIENCE and SOCIETY, 2025)
The article presents work with the SIMULINK package of the MATLAB program. The MATLAB program is an integrated system designed for mathematical and technical engineering calculations. The SIMULINK program has become the most widely used software package in science and industry for modeling and simulation of dynamic systems. Due to the integration of SIMULINK in the MATLAB program, it is possible to model, analyze and correct models from anywhere in its environment.